2022
DOI: 10.3390/ijerph19106255
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Education of Farmers’ Cooperatives on the Adoption of Green Prevention and Control Technologies by Members: Evidence from Rural China

Abstract: The study explores the impact of education of farmers’ cooperatives on members’ green production behavior. The Probit, Oprobit model and the mediation effect model are used to analyze the influence mechanism of the cooperative’s education on the members’ adoption of four types of green prevention and control technologies and the overall adoption rate, and the instrumental variable method is used for endogeneity treatment and robustness test. The results show that: (1) The education of cooperatives have a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…There are significant differences in values and preferences among generations of farmers, and different values influence judgments and behaviors ( Lyons and Kuron, 2014 ; Luo et al, 2022 ). According to the academic standard of dividing the old and new generations farmers and taking into account the actual situation in rural areas, this paper uses 50 years old as the dividing line to classify the new generation and the old generation farmers, and conduct Oprobit and IV-Oprobit regressions on the effect of farmers' cognition of COVID-19 outbreak on farmers' willingness of green production for the two generations respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are significant differences in values and preferences among generations of farmers, and different values influence judgments and behaviors ( Lyons and Kuron, 2014 ; Luo et al, 2022 ). According to the academic standard of dividing the old and new generations farmers and taking into account the actual situation in rural areas, this paper uses 50 years old as the dividing line to classify the new generation and the old generation farmers, and conduct Oprobit and IV-Oprobit regressions on the effect of farmers' cognition of COVID-19 outbreak on farmers' willingness of green production for the two generations respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to the green production willingness of farmers ( Yu et al, 2020 ; Luo et al, 2022a , Luo et al, 2022b ; Gao et al, 2018 ), we control for nine variables including farmers' gender to explore the effect of farmers’ cognition of COVID-19 outbreak on willingness of green production and their mechanisms of action in this paper. The specific meanings and values of the variables are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, this paper selected control variables, including respondents’ individual, household, and cooperative characteristics. Specifically, individual characteristics, such as gender [ 6 ], age [ 3 ], and education level [ 5 ], household characteristics, such as family farming area [ 4 ], number of off-farm laborers [ 27 ], and annual household income [ 28 ], and critical characteristics of cooperatives, such as the establishment time [ 29 ], demonstration level (according to the act ‘Opinions on carrying out the construction action of the farmer’s professional cooperative demonstration’ published by Ministry of Agriculture in 2009, the selection principles of demonstration agricultural cooperatives include management democracy, economic strength, the number of members, and social reputation. From low to high, there are four levels of demonstration agricultural cooperatives, including county-level demonstration, city-level demonstration, province-level demonstration, and national-level demonstration), and available capital [ 30 , 31 ] were included.…”
Section: Methodsmentioning
confidence: 99%
“…Hypothesis 5. Studies have shown that education of farmers can significantly increase farmers' sense of responsibility and reduce farmers' fertilizer use (Ying et al, 2017;Tian et al, 2021;Luo et al, 2022), that moral responsibility, environmental knowledge, and skills can promote farmers' proenvironmental behavior, and that cultivating farmers' sense of moral responsibility and responsibility and running field schools can promote farmers' pro-environmental behavior (Bagheri et al, 2019;Gowda et al, 2021;Khan et al, 2021). Education and training by cooperatives can make smallholder farmers aware of the ecological damage caused by the heavy use of fertilizers and pesticides.…”
Section: Model Hypothesis and Model Constructionmentioning
confidence: 99%